Effects of hypertension in patients receiving mechanical thrombectomy: A meta-analysis. Issue 16 (April 2020) - Yuan, Zhengzhou; Chen, Ning; Zhou, Muke; Guo, Jian; Zhang, Yanan; Li, Yanbo; He, Li
Abstract: Background: Available evidence shows conflicting results with regard to a potential detrimental effect of hypertension on clinical outcomes in patients who undergo mechanical thrombectomy (MT). We performed a meta-analysis to evaluate the impact of hypertension on the prognosis of patients with acute ischaemic stroke (AIS) treated by MT. Methods: We systematically reviewed previous studies in the PubMed, EMBASE, and Cochrane library databases that reported MT outcomes in AIS patients and their relationships with hypertension or blood pressure. We used a poor outcome (modified Rankin score >2 at 3 months) as the primary end point. Mortality and symptomatic intracranial hemorrhage were the secondary end points. We incorporated a random effect for trials in all models. Results: Data from 6650 patients in 31 articles that evaluated the effect of hypertension or blood pressure on outcomes after MT were included. Compared with patients without hypertension, patients with hypertension had significantly higher odds of a poor outcome (odds ratio 0.70; 95% confidence interval 0.57–0.85; I 2 = 43%) and higher mortality (odds ratio 1.70; 95% confidence interval 1.26–2.29; I 2 = 33%). Symptomatic intracranial hemorrhage did not differ by patient hypertension status. Conclusions: The present study confirms that hypertension and high blood pressure are associated with a poor outcome at 3 months after MT in AIS patients. However, the causal relationship between hypertension and a poor outcome remains undetermined, and further investigations are required to ascertain whether AIS patients receiving MT could benefit from intensive blood pressure control. Abstract : Supplemental Digital Content is available in the text